In-line filtration minimizes organ dysfunction: New aspects from a prospective, randomized, controlled trial - Boehne Martin; Jack Thomas; Köditz Harald; Seidemann Kathrin; Schmidt Florian; Abura Michaela; Bertram Harald; Sasse Michael (BMC, 2013)
Abstract Background Infused particles induce thrombogenesis, impair microcirculation and modulate immune response. We have previously shown in critically ill children, that particle-retentive in-line filtration reduced the overall complication rate of severe events, length of stay and duration of mechanical ventilation. We now evaluated the influence of in-line filtration on different organ function and thereby elucidated the potential underlying pathophysiological effects of particle infusion. Methods In this single-centre, prospective, randomized controlled trial 807 critically ill children were assigned to either control (n = 406) or filter group (n = 401), the latter receiving in-line filtration for complete infusion therapy. Both groups were compared regarding the differences of incidence rates and its 95% confidence interval (CI) of different organ dysfunction as defined by the International Pediatric Sepsis Consensus Conference 2005. Results The incidence rates of respiratory (−5.06%; 95% CI, −9.52 to −0.59%), renal (−3.87%; 95% CI, −7.58 to −0.15%) and hematologic (−3.89%; 95% CI, −7.26 to −0.51%) dysfunction were decreased in the filter group. No difference was demonstrated for the occurrence rates of cardiovascular, hepatic, or neurologic dysfunction between both groups. Conclusions In-line filtration has beneficial effects on the preservation of hematologic, renal and respiratory function in critically ill patients. The presented clinical data further support our hypothesis regarding potential harmful effects of particles. In critically ill patients infused particles may lead to further deterioration of the microcirculation, induce a systemic hypercoagulability and inflammation with consecutive negative effects on organ function. Trial registration ClinicalTrials.gov number; NCT00209768